A high-capacity Mg-Cu-Sr-based hydrogen storage alloy catalyzed by nano K2MgF4 and a preparation method thereof

By adding Cu and Sr to the Mg-Cu-Sr hydrogen storage alloy to form an intermetallic compound, and adding nano K2MgF4 catalyst during the ball milling process to form a nanocrystalline-amorphous structure, the insufficient capacity and heat of the existing hydrogen storage materials are solved. The problem of high stability achieves efficient hydrogen absorption and discharge performance and is suitable for hydrogen supply systems of on-board fuel cells.

CN117089749BActive Publication Date: 2024-12-27ZHONGXIN (WEISHAN) RARE EARTH NEW MATERIALS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311083319.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2024-12-27
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

The existing rare earth-based AB5 and Ti Fe-based hydrogen storage materials have insufficient hydrogen storage capacity in fuel cells, the magnesium-based alloy has high thermal stability and poor hydrogen absorption and discharge kinetic performance, making it difficult to meet the requirements of on-board fuel cells.

Method used

Using Mg-Cu-Sr-based hydrogen storage alloy, an intermetallic compound is formed by adding Cu and Sr, and a nano K2MgF4 catalyst is added during the ball milling process to form a nanocrystalline-amorphous structure, improving the hydrogen absorption and release thermodynamics and dynamics of magnesium-based alloys. Learn performance.

Benefits of technology

The hydrogen storage capacity and hydrogen absorption and release kinetic properties are significantly improved, the thermal stability and kinetic properties of the hydride are enhanced, and alloy powder with high efficiency hydrogen absorption and release cycle stability is formed, which is suitable as a hydrogen supply carrier for hydrogen fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117089749B_ABST
    Figure CN117089749B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solid hydrogen storage alloy materials, and provides a nano K2MgF4-catalyzed high-capacity Mg-Cu-S-based hydrogen storage alloy powder for fuel cells containing a small amount of catalyst. The chemical formula of the alloy is: Mg 95 Cu 5‑x Sr x +y(wt)%K2MgF4, where x is the atomic ratio, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid hydrogen storage alloy materials, and in particular provides a high-capacity Mg-Cu-Sr-based hydrogen storage alloy powder for a fuel cell catalyzed by nanometer K2MgF4 and a preparation method thereof. Background Art

[0002] The contents in the background technology that reflect the process of the inventor discovering and analyzing the problem should not necessarily be regarded as prior art.

[0003] The application of hydrogen fuel cells in the automotive field has attracted great attention from all over the world. An efficient and safe hydrogen supply system is one of the technical keys of fuel cells. At present, most hydrogen supply systems of fuel cells use high-pressure gaseous hydrogen storage. Due to the high technical requirements for pressure vessels and users' concerns about the safety of high-pressure systems, researchers are forced to develop safer and more reliable hydrogen supply systems. Researchers have turned their attention to low-pressure solid hydrogen storage materials and have found that a variety of solid hydrogen storage materials have the potential for fuel cell applications. Among them, the rare earth-based AB5-type hydrogen storage material has good hydrogen absorption and desorption kinetics and can meet the requirements of fuel cells. However, the alloy system is limited in its application in fuel cells due to its low theoretical hydrogen storage capacity (1.4%). Although the theoretical capacity (1.86%) of TiFe-based hydrogen storage materials is higher than that of AB5-type alloys, it still cannot meet the requirements of automotive fuel cells.

[0004] Magnesium and magnesium-based alloys have attracted much attention from researchers due to their extremely high hydrogen storage capacity (7.6%). At the same time, magnesium is abundant in reserves and low in cost. In terms of hydrogen storage capacity, it fully meets the requirements of vehicle fuel cells. However, magnesium hydride has extremely high thermal stability, its decomposition temperature is >300°C, and the formation and decomposition kinetics of hydride are extremely poor, making the hydrogen absorption and desorption kinetics unsatisfactory. Summary of the invention

[0005] The purpose of the present invention is to provide a solid hydrogen storage alloy for Mg-Cu-Sr-based fuel cells with high capacity and excellent hydrogen absorption and desorption kinetics and a preparation method thereof. Through the present invention, the hydrogen storage performance of the magnesium-based alloy is greatly improved. Thus, a nanocrystalline-amorphous Mg-Cu-Sr-based hydrogen storage alloy with high hydrogen storage capacity and excellent kinetics and a corresponding preparation process are provided. The present invention achieves the above-mentioned objectives through the following technical routes.

[0006] The first aspect of the present invention provides a multi-component Mg-Cu-Sr based hydrogen storage alloy for a fuel cell, the alloy contains the elements Cu and Sr, a small amount of K2MgF4 catalyst, and the composition is Mg 95 Cu 5-x Sr x+y wt.% of K2MgF4, where x is the atomic ratio, 0 < x ≤ 2, y is the percentage of K2MgF4 in the alloy, 2 ≤ y ≤ 8, and preferably x = 1.5, y = 5.

[0007] On the other hand, the present invention provides a method for preparing a hydrogen storage alloy for a fuel cell, and the preparation steps include:

[0008] A Batching: According to the chemical composition formula Mg 95 Cu 5-x Sr x (x = 0, 0.5, 1, 1.5, 2) for batching, where x is the atomic ratio. Among them, when batching according to the chemical composition formula, the Mg element has a burn loss of 8%, and the purity of the raw materials is greater than 99.6%.

[0009] B Melting: Place the prepared raw materials in a magnesia crucible in sequence, evacuate to 1×10 -2 -5×10 - 4 Pa, introduce an inert gas with a pressure of 0.01 - 0.1 MPa as the protective gas. The protective gas is pure helium or a helium + argon mixed gas, and the volume ratio of the mixed gas is about 1:1. Use a conventional heating method, such as arc melting, induction heating melting or other heating methods. The heating conditions are: the heating temperature is 1400 - 1550 °C to obtain a molten liquid master alloy, and keep it in the molten state for 3 - 5 minutes; then pour the melted alloy into a water-cooled copper mold to obtain a cast master alloy ingot.

[0010] C Rapid quenching: Place the alloy ingot prepared in step B above in a quartz tube with a slit at the bottom, and use induction heating under helium protection to completely melt the alloy ingot. Use the pressure of the protective gas to spray it out from the slit at the bottom of the quartz tube and land on the surface of a water-cooled copper roller rotating at a linear speed of 20 m / s to obtain a rapidly quenched alloy thin sheet with a thickness of about 50 - 100 μm.

[0011] D Mechanical ball milling: After mechanically crushing the rapidly quenched Mg 95 Cu 5-x Sr x alloy thin strip and passing it through a 200-mesh sieve, load it into a stainless steel ball milling tank together with the nano-K2MgF4 catalyst, evacuate and then fill it with high-purity argon, and ball mill it in an all-round planetary high-energy ball mill for 2 - 5 hours (excluding downtime), with a ball-to-material ratio of 1:20 and a rotation speed of 350 revolutions per minute. During the ball milling process, the ball mill stops for 0.5 hours every 1 hour of operation to prevent the temperature of the ball milling tank and the abrasive from being too high.

[0012] The phase structure of the ball-milled powder was tested by XRD, the morphology and microstructure of the ball-milled alloy particles were observed by high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM), and the crystalline state of the alloy was determined by selected area electron diffraction (SAED). The solid hydrogen storage capacity and hydrogen absorption and desorption kinetics of the alloy powder were tested by semi-automatic Si everts equipment. The hydrogen absorption and desorption temperature was 280℃, the initial hydrogen pressure of hydrogen absorption was 3MPa, and the desorption temperature was 1×10 -4 MPa pressure.

[0013] The beneficial effects of the present invention are:

[0014] In the alloy material, the present invention adds Cu and Sr for alloying, Mg and Cu form Mg2Cu phase, Sr and Cu form CuSr phase and Cu5Sr phase, and the formed intermetallic compound can significantly improve the thermodynamic and kinetic properties of hydrogen absorption and desorption of magnesium alloy. A special microstructure with nanocrystalline + amorphous is obtained by rapid quenching. This structure has obvious advantages in improving the kinetic properties of hydrogen absorption and desorption of Mg-based alloys. A trace amount of nano K2MgF4 catalyst is added, and the catalyst is evenly distributed on the surface of alloy particles by mechanical ball milling. Since K2MgF4 has high activity, it has a very beneficial effect on improving the thermodynamic properties of hydrogen absorption and desorption of magnesium-based alloys. The hydrogen storage alloy powder prepared in this way not only has high hydrogen absorption and desorption capacity and excellent hydrogen absorption and desorption kinetics, but also has good hydrogen absorption and desorption cycle stability, and is very likely to become a hydrogen supply carrier for hydrogen fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a diagram of the cast alloy ingot of Example 1;

[0016] Figure 2 It is a diagram of the rapidly quenched alloy ribbon of Example 1;

[0017] Figure 3 XRD patterns of the as-cast alloys of Examples 1-5;

[0018] Figure 4 The SEM morphology of the ball-milled powders of Examples 1-4;

[0019] Figure 5 The XRD patterns of the ball-milled powders of Examples 1-8;

[0020] Figure 6 HRTEM morphology of the ball-milled alloys of Examples 1-4. DETAILED DESCRIPTION

[0021] The following will describe the implementation methods of the present application in detail with the help of accompanying drawings and examples, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0022] It is found through research in the present invention that the multiphase structure can increase the density of grain boundaries and phase boundaries, improve the diffusion ability of hydrogen atoms, shorten the diffusion distance of hydrogen atoms, and thus improve the kinetics of hydride formation and decomposition. At the same time, the alloy containing multiple components can significantly reduce the thermal stability of hydrides and improve the hydrogen desorption thermodynamics of the alloy. In terms of the composition design of the alloy, adding a small amount of Cu and Sr can form phases such as Mg2Cu, CuSr, and Cu5Sr, significantly improving the hydrogen absorption and desorption kinetics of the magnesium-based alloy and to a certain extent improving the hydrogen absorption and desorption thermodynamics of the alloy. At the same time, adding a highly active catalyst K2MgF4 can form a highly active coating layer on the surface of magnesium alloy particles through mechanical ball milling, reduce the thermal stability of magnesium hydride, and improve the hydrogen absorption and desorption kinetics of the alloy. Research shows that improving the microstructure of the alloy and increasing crystal defects can significantly enhance the hydrogen absorption and desorption kinetics of the alloy. In particular, the formation of nanocrystals and a small amount of amorphous structure in the alloy is extremely beneficial to improving the hydrogen absorption and desorption kinetics of the alloy. Increasing the density of crystal defects, especially increasing dislocations, stacking faults, etc., is extremely beneficial to the nucleation and growth of hydrides, thereby improving the hydrogen absorption and desorption kinetics of the alloy.

[0023] In terms of the preparation process, first, the master alloy is subjected to rapid quenching treatment to obtain a nanocrystal + amorphous structure and form rapid quenching crystal defects in the alloy. Research shows that the crystal defects formed by rapid quenching have higher stability than ball milling defects, which is beneficial to improving the hydrogen absorption and desorption cycle stability of the alloy. Adding a small amount of catalyst to the rapidly quenched alloy and performing ball milling can improve the surface characteristics of the alloy, increase the defects on the alloy surface, and further improve the hydrogen absorption and desorption thermodynamics and kinetics of the alloy.

[0024] The present invention further illustrates the composition and preparation method of the magnesium-based hydrogen storage alloy for fuel cells involved in the present invention through the following examples.

[0025] The composition chemical formula of the magnesium-based hydrogen storage alloy for fuel cells of the present invention is: Mg 95 Cu 5-x Sr x + y wt.% K2MgF4, where x is the atomic ratio, 0 < x ≤ 2, and preferably x = 1.5. y is the percentage of K2MgF4 in the alloy, 2 ≤ y ≤ 8, and preferably y = 5. wt.% represents weight percentage.

[0026] The preparation method of the high-capacity hydrogen storage alloy for fuel cells of the present invention includes the following steps:

[0027] A. Weigh the ingredients according to the chemical formula composition Mg 95 Cu 5-x Sr x Since magnesium is easy to volatilize, an 8% burn loss is added during the proportioning.

[0028] B. Place the prepared raw materials in a magnesium oxide crucible, place the block of metal magnesium on the top of the crucible, and add other materials to the crucible in any order. Use induction heating for melting and evacuate to 1×10 -2 -5×10 -4 Pa, and then fill with 0.01-0.1MPa high-purity helium as a protective gas. In order to reduce costs, argon + helium mixed gas can also be used as a protective gas, and the volume ratio of the mixed gas is about 1:1. The melting temperature is 1400-1550℃. The temperature is adjusted according to the composition of the alloy to ensure that the metal raw materials are completely melted. After keeping warm for 3-5 minutes, the molten alloy is poured into a water-cooled copper mold to obtain a cast master alloy ingot.

[0029] C. The ingot prepared in the above step B is placed in a quartz tube with a slit at the bottom, and is heated by medium frequency induction until the ingot is completely melted. The liquid alloy is ejected from the bottom slit using the pressure of the protective gas and falls on the surface of a water-cooled copper roller rotating at a linear speed of 20 m / s to obtain a rapidly quenched alloy sheet with a thickness of about 50-100 μm.

[0030] D. Rapidly quench Mg 95 Cu 5-x Sr x After the alloy is mechanically crushed and passed through a 200-mesh sieve, it is mixed with a nano K2MgF4 catalyst and loaded into a stainless steel ball mill. After vacuuming, high-purity argon is filled in and ball milled in an all-round planetary high-energy ball mill for 2-5 hours (excluding downtime); the ball-to-material ratio is 1:20 and the speed is 350 rpm. During the ball milling process, the mill is stopped for 0.5 hours for every 1 hour of ball milling to prevent the ball mill and the abrasive from being too hot. The preferred ball milling time is 3 hours, and the alloy powder described in the patent is obtained.

[0031] F. The structure of the ball-milled powder was tested by XRD, the morphology and microstructure of the alloy particles before and after hydrogen absorption were observed by high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM), and the crystalline state of the alloy was determined by selected area electron diffraction (SAED). The solid hydrogen storage capacity and hydrogen absorption and desorption kinetics of the alloy powder were tested by fully automatic Si everts equipment. The hydrogen absorption temperature was 280°C, the initial hydrogen pressure of hydrogen absorption was 3MPa, and the desorption was carried out at 280°C and 1×10 -4 MPa pressure.

[0032] The chemical composition and proportion of the specific embodiment of the present invention are selected as follows:

[0033] Example 1: Mg 95 Cu 3.5 Sr 1.5 +5wt.%K2MgF4

[0034] Example 2: Mg95 Cu3Sr2+2wt.%K2MgF4

[0035] Example 3: Mg 95 Cu4Sr1+4wt.%K2MgF4

[0036] Example 4: Mg95Cu5+3wt.%K2MgF4

[0037] Example 5: Mg 95 Cu 4.5 Sr 0.5 +7wt.%K2MgF4

[0038] Example 6: Mg 95 Cu 3.5 Sr 1.5 +8wt.%K2MgF4

[0039] Example 7: Mg 95 Cu 3.5 Sr 1.5 +3wt.%K2MgF4

[0040] Example 8: Mg 95 Cu 3.5 Sr 1.5 +6wt.%K2MgF4

[0041] According to the chemical formula composition of each embodiment, block metal magnesium, metal copper and metal strontium are selected. The metal purity requirement is ≥99.5%. After the selected block metal is polished to remove the surface oxide layer, it is weighed according to the chemical dosage ratio. Among them, the metal magnesium is increased by 8wt.% in the proportion to compensate for the burn loss during melting; in the preparation process, the technical parameters of each stage are as follows: vacuum is evacuated to 1×10 -2 -5×10 -4 Pa, filled with high-purity helium with a pressure of 0.01 to 0.1 MPa or a helium + argon mixed gas with a volume ratio of 1:1; the melting temperature is 1400-1550℃; the vacuum is evacuated to 10 -2 -10 -4 Pa, the surface linear speed of the water-cooled copper roller is 20m / s. The quenched thin slices are mechanically crushed and passed through a 200 mesh sieve, mixed with the nano K2MgF4 catalyst and loaded into a stainless steel ball mill, and ball milled for 2-5 hours with an omnidirectional planetary ball mill, and the ball mill is stopped for 0.5 hours every 1 hour of operation. All process parameters can be appropriately selected within the above range to prepare the hydrogen storage alloy powder described in the patent. Therefore, although the present invention only cites a typical embodiment, this embodiment is applicable to preparation methods with different parameters.

[0042] Process parameters of Example 1: According to the chemical formula Mg95 Cu 3.5 Sr 1.5 , select bulk metal magnesium, metal copper and metal strontium. The purity of these metals is 99.8%. They are weighed according to the chemical dosage ratio, including 959.5 grams of metal magnesium, 85.6 grams of metal copper and 28.0 grams of metal strontium. The weighed bulk metals are placed in the magnesium oxide crucible of the medium frequency induction furnace, and then the furnace cover is closed and vacuumed for about 30 minutes to a vacuum degree of 5×10 -2 Pa, and then fill with high-purity helium protective gas until the pressure reaches -0.04MPa, adjust the power to 5kW, control the temperature at 650℃, melt the metal Mg, and then adjust the power to 25kW, control the temperature at 1550℃, melt the metal copper and strontium. After keeping warm in the molten state for 5 minutes, pour the molten liquid into the copper mold, and adjust the power to 8kW when injecting it into the ingot mold. Cool it in the helium protective atmosphere for 30 minutes and then take it out of the furnace to obtain a cylindrical ingot with a diameter of 30mm.

[0043] Cast Mg 95 Cu 3.5 Sr 1.5 About 100 grams of alloy rods were placed in a quartz tube with a diameter of 35 mm and a slit of 0.05 mm×20 mm at the bottom; the alloy was heated to melt by radio frequency of 245 kHz, and the heating power was 15 kW under the protection of helium atmosphere; the molten alloy was sprayed onto the surface of a water-cooled copper roller with a surface linear velocity of 20 m / s at a helium pressure of 1.05 atm to obtain a rapidly quenched alloy strip with a thickness of about 85 μm;

[0044] The rapid quenching of Mg 95 Cu 3.5 Sr 1.5 The alloy flakes were mechanically crushed and passed through a 200-mesh sieve. 20 g of the sieved alloy powder, 1 g of nano K2MgF4 catalyst and 400 g of stainless steel grinding balls were placed in a 250 ml stainless steel ball milling jar, which was evacuated and sealed after being filled with high-purity argon. The jar was ball milled for 3 hours in an all-round planetary high-energy ball mill. The machine was stopped for 0.5 hours for every 1 hour of ball milling.

[0045] Figure 1 The ingot of Example 1 is macroscopically observed through the fracture of the ingot, and it is found that the cross-section of the ingot alloy has uniform composition without macroscopic segregation.

[0046] Figure 2 The alloy ribbon is in the rapid quenching state. The thickness of the tested ribbon is about 85 μm. The structure of the alloy ribbon treated by rapid quenching is nanocrystalline + a small amount of amorphous structure.

[0047] Figure 3The XRD patterns of the cast alloys of Examples 1-8 show that the addition of Cu and Sr forms a variety of intermetallic compounds, including Mg2Cu, CuSr, and Cu5Sr;

[0048] Figure 4 The SEM morphology of the ball-milled powder of Examples 1-4 shows that the alloy particles are well dispersed after ball milling, and no obvious agglomeration occurs, which is obviously related to the effect of the catalyst. No catalyst K2MgF4 is observed, and it can be inferred that it is evenly distributed on the surface of the ball-milled alloy particles. Since K2MgF4 is very soft, it is impossible to cut into the interior of the alloy particles during the ball milling process.

[0049] Figure 5 The XRD spectra of the ball-milled alloys of Examples 1-8 show that the ball-milled materials have nanocrystalline and amorphous structural characteristics, and XRD does not show the existence of free K2MgF4, indicating that through ball milling, the catalyst and the matrix alloy form a consistent nanocrystalline structure.

[0050] Figure 6 The HRTEM morphology of the ball-milled alloys of Examples 1-4 shows that the alloys have nanocrystalline and amorphous structures.

[0051] The gaseous hydrogen absorption and desorption capacity and kinetics of the alloy powder were tested using a fully automatic Sieverts device. The results are shown in Table 1.

[0052] Table 1 Hydrogen absorption and desorption kinetics and cycle stability of alloy powders with different compositions

[0053]

[0054] — Hydrogen absorption within 10 minutes at an initial hydrogen pressure of 3 MPa and 280°C (wt.%), —At an initial pressure of 1×10 -4 MPa and 280℃, the amount of hydrogen released within 30 minutes (wt.%) 100 =C 100 / C max × 100%, where C max is the saturated hydrogen absorption capacity of the alloy, C 100 Hydrogen absorption after the 100th cycle.

[0055] The above results show that the ball-milled alloy powder has high hydrogen absorption and desorption capacity and excellent dynamic performance. Obviously, the hydrogen absorption and desorption capacity of the alloy of the present invention can fully meet the hydrogen capacity requirements of the fuel cell for the hydrogen supply system. Compared with the existing similar alloys, the hydrogen storage performance of the alloy of the present invention has been significantly improved.

[0056] According to analysis, alloying can significantly improve the thermodynamic and kinetic properties of hydrogen absorption and desorption of magnesium-based alloys. The improvement of microstructure and the formation of crystal defects further improve the kinetic properties of hydrogen absorption and desorption of magnesium-based alloys. Mechanical ball milling is considered to be the most effective preparation technology for the formation of nanocrystalline and amorphous structures. Adding a small amount of active catalyst can significantly improve the thermodynamic and kinetic properties of hydrogen absorption and desorption of magnesium-based alloys.

[0057] The present invention adopts multi-element alloying in component design to form a special intermetallic compound, and adds a small amount of nano K2MgF4 as a catalyst during the ball milling process to obtain a powder with a nanocrystalline-amorphous structure, which greatly improves the thermodynamic and kinetic properties of hydrogen absorption and desorption of the magnesium-based alloy.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-capacity Mg-Cu-Sr-based hydrogen storage alloy catalyzed by nano K2MgF4 for fuel cells, characterized in that: Containing Cu, Sr and nano-catalyst K2MgF4, and its chemical formula composition is: Mg 95 Cu 5-x Sr x + y wt.% K2MgF4, where x is the atomic ratio, 0 < x ≤ 1.5, y is the percentage of K2MgF4 in the alloy, 3 ≤ y ≤ 7; the nano-K2MgF4 catalyst is uniformly distributed on the surface of the alloy particles by mechanical ball milling.

2. The high-capacity Mg-Cu-Sr-based hydrogen storage alloy catalyzed by nano K2MgF4 for fuel cells according to claim 1, characterized in that: The atomic ratio of the chemical formula is: x=1.5; the content of the catalyst K2MgF4 is y=5.

3. The method for preparing a high-capacity Mg-Cu-Sr-based hydrogen storage alloy catalyzed by nano K2MgF4 for a fuel cell according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: According to the chemical formula Mg 95 Cu 5-x Sr x The ingredients are prepared, where x is the atomic ratio, 0 <x≤1.5; Step 2: Use induction heating to melt all elements to obtain molten Mg 95 Cu 5-x Sr x Alloy; its heating and melting conditions are: heating temperature 1400-1550 o C, the molten alloy is poured into a copper mold under the protection of high-purity helium gas with a melting environment of 0.01 to 0.1 MPa to obtain a cast master alloy ingot; Step 3: Place the ingot prepared in the above step 2 in a quartz tube with a slit at the bottom, heat it again to a molten state with an induction coil, and spray it from the slit at the bottom of the quartz tube using the pressure of the protective gas, and continuously spray it on the smooth surface of a copper roller rotating at a linear speed of 20 m / s to obtain a rapidly quenched alloy thin strip; Step 4: Rapidly quench Mg 95 Cu 5-x Sr x The alloy is mechanically crushed and passed through a 200-mesh sieve, mixed with nano K2MgF4 catalyst and stainless steel grinding balls and loaded into a stainless steel ball mill. After vacuuming, high-purity argon is filled in and ball milled in an all-round planetary high-energy ball mill for 2-5 hours, with a ball-to-material ratio of 1:

20.

4. The method for preparing a high-capacity Mg-Cu-Sr-based hydrogen storage alloy catalyzed by nano K2MgF4 for a fuel cell according to claim 3, characterized in that: The rapidly quenched alloy thin strip has a nanocrystalline-amorphous structure and a thickness of 50-100 μm.

Citation Information

Patent Citations

  • Nanometer TiF3 catalyzed high-volume hydrogen-storing alloy and preparation method thereof

    CN103667837A

  • Biomedical degradable absorption Mg-Sr-Cu alloy material, preparation method and application

    CN104762542A

  • Mg-Al-Y-based hydrogen storage material and preparation method thereof

    CN113862536A